Dynamic changes in the proximitome of neutral sphingomyelinase-2 (nSMase2) in TNFα stimulated Jurkat cells - Schöl, Marie; Schempp, Rebekka; Hennig, Thomas; Wigger, Dominik; Schumacher, Fabian; Kleuser, Burkhard; Stigloher, Christian; van Ham, Marco; Jänsch, Lothar; Schneider-Schaulies, Sibylle; Dölken, Lars; Avota, Elita (Frontiers in Immunology, 2024)
Ceramides generated by the activity of the neutral sphingomyelinase 2 (nSMase2) play a pivotal role in stress responses in mammalian cells. Dysregulation of sphingolipid metabolism has been implicated in numerous inflammation-related pathologies. However, its influence on inflammatory cytokineinduced signaling is yet incompletely understood. Here, we used proximity labeling to explore the plasma membrane proximal protein network of nSMase2 and TNFα-induced changes thereof. We established Jurkat cells stably expressing nSMase2 C-terminally fused to the engineered ascorbate peroxidase 2 (APEX2). Removal of excess biotin phenol substantially improved streptavidin-based affinity purification of biotinylated proteins. Using our optimized protocol, we determined nSMase2proximal biotinylated proteins and their changes within the first 5 min of TNFα stimulation by quantitative mass spectrometry. We observed significant dynamic changes in the nSMase2 microenvironment in response to TNFα stimulation consistent with rapid remodeling of protein networks. Our data confirmed known nSMase2 interactors and revealed that the recruitment of most proteins depended on nSMase2 enzymatic activity. We measured significant enrichment of proteins hat formatiert: Schriftart: 16 Pt. related to vesicle-mediated transport, including proteins of recycling endosomes, trans-Golgi network, and exocytic vesicles in the proximitome of enzymatically active nSMase2 within the first minutes of TNFα stimulation. Hence, the nSMase2 proximal network and its TNFα-induced changes provide a valuable resource for further investigations into the involvement of nSMase2 in the early signaling pathways triggered by TNFα.\* MERGEFORMAT } such as agonist-activated G-protein coupled receptors or antigen-induced changes after B-cell receptor activation { ADDIN EN.CITE { ADDIN EN.CITE.DATA }}.To explore the PM proximal network of nSMase2 and TNFα-induced changes thereof, we generated Jurkat cells stably expressing the nSMase2-APEX2 fusion protein. First, we tried to validate the APEX2 approach by proteomic analysis of nSMase2 proximal proteins under steady-state conditions. Recently, we published the lipid droplet protein PLIN3 as one of the most highly enriched proteins in the proximity of the nSMase2-APEX2 { ADDIN EN.